Automated Microdosing System for Integration With a Miniaturized High-pressure Reactor System. Issue 4 (11th December 2005) - Stoll, Norbert; Hawali, Ihsan; Thurow, Kerstin
Abstract : We present a new automated dosing system developed by the Institute for Automation of the University of Rostock, Germany. The new system is designed for the dosing of chemical liquids in the range of 50 μ L–2.5 mL. It is integrated into a miniaturized reactor system to be used in the field of combinatorial synthesis. The reactor system can be pressurized up to 150 bar and tempered up to 200°C. A wide range of liquids with different physical properties can be handled with the new dosing system. A detailed description of the new dosing system in terms of function and operation as well as the relevant features and potential benefits is provided.